Update on Perioperative Prevention of Cardiac Surgery-Associated Acute Kidney Injury - Luis Baeza; Pablo Avanzas; Carla Delgado-Martí; Manuel García-Delgado; Santiago Gómez-Estanga; José M. López González; Pablo Montero-López; Marc Vives (Journal of Clinical Medicine, 2026)
Cardiac surgery-associated acute kidney injury (CS-AKI) increases short- and long-term mortality, progression to chronic kidney disease (CKD), and healthcare costs. Its pathogenesis is multifactorial—combining renal hypoperfusion, impaired oxygen delivery, hemodilution, inflammation, ischemia–reperfusion injury, and nephrotoxin exposure—so no single intervention confers universal protection. This narrative review appraises fourteen perioperative prevention strategies, grading each by study design, reproducibility, and concordance with contemporary guidelines. The strongest actionable evidence supports the preservation of renal oxygen delivery during cardiopulmonary bypass through goal-directed perfusion, perioperative amino acid infusion, and biomarker-guided Kidney Disease: Improving Global Outcomes (KDIGO) care bundles. Remote ischemic preconditioning, pulsatile flow, minimally invasive extracorporeal circulation, dexmedetomidine, N-acetylcysteine, levosimendan, hemoadsorption with the oXiris membrane, and natriuretic peptides show variable or subgroup-dependent signals limited by heterogeneous trial design and acute kidney injury (AKI) definitions. Prevention of CS-AKI is, therefore, best conceived as a multimodal, patient-centered process integrating preoperative risk stratification, intraoperative oxygen delivery optimization, patient blood management (PBM), and postoperative nephrotoxin avoidance and surveillance.